African Small and Medium Enterprises, Networks, and Manufacturing Performance - Biggs, Tyler; Shah, Manju Kedia (World Bank, Washington, DC, 2012)
This paper examines the role of private support institutions in determining small and medium enterprise (SME) growth and performance in Sub-Saharan Africa (SSA). It finds that SMEs in SSA get around market failures and lack of formal institutions by creating private governance systems in the form of long-term business relationships and tight, ethnically-based, business networks. There are important links between these informal governance institutions and SME performance. Networks raise the performance of "insiders" and, in the sparse business environments of the SSA region, have attendant negative consequences for market participation of "outsiders," such as indigenous African SMEs. This is indicated through the determinants of access to supplier credit. Policy interventions will be needed to improve the platform for relation-based governance mechanisms and to address the exclusionary effects of tight networks.